Myanmar: the country that ‘has it all’ - Susan Banki (Jember University Press, 2020)
For scholars of Southeast Asia interested in human rights, Myanmar is a country that ‘has it all.’ I use this tongue-in-cheek expression to suggest the myriad ways that the country remains mired in structural challenges that inform its current human rights problems. In this paper, I point out the country’s most glaring structural challenges and link these to its most pressing human rights problems. A brief section about Myanmar in the context of COVID-19 offers the same conclusion as the rest of the article: while there is variance in the actors targeted and the degree of suppression, the underlying patterns of oppression remain unchanged over time.